Gestational diabetes mellitus: Confusion among medical doctors caused by multiple international criteria. Issue 6 (29th December 2014) - Agarwal, Mukesh M.; Shah, Syed M.; Al Kaabi, Juma; Saquib, Shabnam; Othman, Yusra
Abstract Aim The aim of this study was to appraise the current regional practices of screening, diagnosis and follow‐up of gestational diabetes mellitus (GDM) because the approach to GDM is frequently inconsistent. Material and Methods A 21‐item questionnaire was distributed to physicians taking care of pregnant women in seven hospitals in the United Arab Emirates and one hospital in Oman. Besides assessing their attitudes towards testing for GDM, the questionnaire assessed familiarity with the Hyperglycemia and Pregnancy Outcome study and the International Association of Diabetes in Pregnancy Study Groups GDM guidelines. Results One hundred and forty‐eight (93%) of the 159 questionnaires distributed to the medical doctors (106 [72%] obstetricians and 42 [28%] internists) were returned. For GDM screening, six hospitals used five different tests; two hospitals utilized one single test. For GDM diagnosis, six hospitals employed the 2‐h, 75‐g oral glucose tolerance test (OGTT) (four different criteria) while two hospitals used the 3‐h, 100‐g OGTT (single criteria). For post‐delivery follow‐up, the 2‐h, 75‐g OGTT and fasting plasma glucose were accepted by 103 (70%) and 38 (26%) of the 148 medical doctors, respectively. Ninety‐eight (69%) of 143 responding physicians were aware of the Hyperglycemia and Pregnancy Outcome study, while 85 (61%) of 140 responders were familiar with the guidelines of the International Association of Diabetes in Pregnancy Study Groups; this knowledge was independent of specialty, seniority, academia, years in practice or country trained. Conclusions Although this study is parochial, its implications are global; that is, further education of caregivers would make the discordant approach to GDM (within and between hospitals) more harmonious and improve the obstetric care of pregnant women.